Fundamentals of mobile and pervasive computing - Adelstein, Frank (McGraw-Hill professional engineering. Communications engineering., 2005)
The authoritative, general reference that has been sorely missing in the field of mobile computing This book teaches all the main topics via the hottest applications in a rapidlygrowing field. ""Big picture"" explanations of ad hoc networks and service discovery Exercises, projects, and solutions to illustrate core concepts Extensive wireless security methodologies